Symposium 2: Assembling university learning technologies for an open world: Connecting institutional and social networks - Hannon, John; Riddle, Matthew; Ryberg, Thomas (Proceedings of the International Conference on Networked Learning, 2014)
This paper considers the emergence of social media in university teaching and learning and the capacity or universities – as complex organisations with disparate interacting parts – to respond to the shift of pedagogies and practices to open networks. Institutional learning technology environments reflect a legacy of prescriptive, hierarchical arrangements associated with enterprise systems, and are a poor fit with the heterarchical and self-organised potential for learning associated with social media and open education practices. In this paper we focus on the tensions that arise from the juxtaposition of these two orientations to learning technologies, and focus on how an emerging online sociality can destabilise established boundaries of learning and connect to other domains of practice. To do this, we examined data from three separate case studies in which participants - both teaching staff and students - reported on student engagement in learning involving social networking activity. We draw on empirical data on student practices that challenge institutional arrangements for learning, and offer insights into the assembly of extended connections for networked learning, in particular the pedagogies of collaboration, knowledge co-construction, and informal social learning. From these instances we draw attention to the interplay of competing metaphors and practices in the organisation as it encounters the potential of more open pedagogies over social and digital networks. Drawing on spatial descriptions of networked learning, we apply Callon’s (1998) notions of framing and overflows to this interplay in order to ask how learning environments were assembled and ordered: what pre-existing configurations were brought to frame and set boundaries for these networks of formal learning; and what activities overflow those boundaries and destabilise these framings. We argue that the adoption of social media by students requires a challenge to the institutional metaphors of containment that implement a default bounded environment. This involves a reappraisal of established learning environments for their pedagogical metaphors and spatial orderings that frame learning, followed by different organisational approaches to account for and enact learning that emerges from the connections, mobilities and flows of social networks. We propose a less integrated, “assembly” approach to institutional learning that attends to the open, fluid connections of networked learning. A spatial articulation of networked learning that bridges both institutional and social networks can equip the university to meet the critical challenges of emerging hybrid learning environments and the potential of more open learning environments.